Yona of the dawn. 28 - Kusanagi, Mizuho, 1979-; MacFarlane, Ysabet Reinhardt (Shojo beat manga., 2021)
After Yona and her friends save the Fire Tribe from an invasion by the Kai Empire, word of their prowess spreads amongst those with deep faith in the Crimson Dragon King. Yona and the gang take cover at Saika Palace, but what trouble awaits when Su-won's advisor Keishuk shows up to guard the Fire Tribe border?